‘The Role of Financial Crises Management Implementing on Investment Development in Kurdistan Region – Iraq During Financial Crises (ISIS War Crisis and COVID-19 Pandemic Crisis)’ - Khudhur, Lavin L.; Khoshnaw , Dr. Aras Q. (Polytechnic Journal of Humanities and Social Sciences, 2024)
This study aims to examine the role of crisis management in managing and handling the financial crises (ISIS war crisis and COVID-19 pandemic crisis) on investment development. As well as, the study examined the influence of the crises on investment development. An analytical and comparative study in the Kurdistan Region-Iraq. This study tries to determine the role of crisis management depending on mitroff’s-five stages model, depending on the regulation and decisions made during the occurrence of the crises. As well as, the study compared the government’s reaction at each stage in both crises era. Also, the study tries to analyze and explore the reality of the investment situation during the occurrence of crises in the region. A conceptual study theme was designed, and a set of hypotheses was developed. To verify the validity of the hypotheses. for that purpose, the financial analysis and SPSS version 28.0 was used. The study reached a set of conclusions, the KRG has more effective and better crisis management to handle and manage the COVID-19 pandemic crisis than the ISIS war crisis on investment projects depending on the scientific criteria. By another hand, the crises themselves there were different from each other. ISIS is a war crisis and external threat. Thus, the ISIS war crisis has a great negative influence on investment projects. capital in dollars dropped from the appearance of ISIS in the crisis stage by (65.20%). As well as, the number of projects dropped from (108) to (70) projects. However, the COVID-19 crisis was a global epidemic spread all over the world but for the region it was internal threat. Causing the delay or stoppage of the projects temporarily rather than that fall the projects. Thus, The COVID-19 pandemic has a limited influence on investment projects. Thus, capital in dollars decreased slightly from the appearance of COVID-19 in the crisis stage by (18.76%). However, the number of projects increased slightly from (66) to (76) projects. The researcher suggested that Manage the crisis according to scientific criteria. And Implementing (Early warning system) to inform the projects of the occurrence of any unwanted events. Keywords: financial crises, crisis management, investment, ISIS war crisis, COVID-19 pandemic crisis, KRG.